Cities going green a handbook of best practices - Kemp, Roger L.; Stephani, Carl J. (McFarland & Company, 2011)
"This is a guide to introduce the rapidly evolving field of communities that are effectively "going green." An assessment of the future of these towns and cities and resources for citizens and officials seeking information conclude the work. This handbook makes an excellent resource for anyone seeking to facilitate the restoration of the natural environment within their community"--Provided by publisher.